2004
DOI: 10.1128/jvi.78.6.3110-3122.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Uncoating of Vector Genomes Is the Key toEfficient Liver Transduction with Pseudotyped Adeno-Associated VirusVectors

Abstract: Transduction of the liver with single-stranded adeno-associated virus serotype 2 (AAV2) vectors is inefficient; less than 10% of hepatocytes are permissive for stable transduction, and transgene expression is characterized by a lag phase of up to 6 weeks. AAV2-based vector genomes packaged inside AAV6 or AAV8 capsids can transduce the liver with higher efficiency, but the molecular mechanisms underlying this phenomenon have not been determined. We now show that the primary barrier to transduction of the liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
264
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(287 citation statements)
references
References 34 publications
23
264
0
Order By: Relevance
“…Transgene expression from AAV2 vectors is known to increase gradually over several weeks and to persist for months or years. [25][26][27] Consistent with this, at 2 weeks postinjection, there was little detectable human TPP-I protein in the rat striatum, but by 1 month, abundant human TPP-I protein was observed. The high level, stable AAV2-mediated expression of human TPP-I in the rat striatum persisted at comparable volume and intensity at 4, 8, 12, and 18 months ( Figure 5).…”
Section: Aav-mediated Cns Transfer Of Cln2 D Sondhi Et Almentioning
confidence: 58%
“…Transgene expression from AAV2 vectors is known to increase gradually over several weeks and to persist for months or years. [25][26][27] Consistent with this, at 2 weeks postinjection, there was little detectable human TPP-I protein in the rat striatum, but by 1 month, abundant human TPP-I protein was observed. The high level, stable AAV2-mediated expression of human TPP-I in the rat striatum persisted at comparable volume and intensity at 4, 8, 12, and 18 months ( Figure 5).…”
Section: Aav-mediated Cns Transfer Of Cln2 D Sondhi Et Almentioning
confidence: 58%
“…89 However, it is possible that differences in kinetics of vector uncoating among various AAV serotypes may influence the presentation of capsid epitopes on MHC-I molecules, thereby inducing differential CTL responses toward transduced cells. 90 Vectors based on AAV serotype 2 have been reported to uncoat slowly, thus potentially allowing processed capsid peptides to be presented by MHC-I. Serotypes that uncoat quickly might not display capsid proteins for the same amount of time or avoid presentation on the MHC-I surface of transduced cells.…”
Section: T-cell Responses To the Aav Capsid: A New Challengementioning
confidence: 99%
“…For example, a recent report has suggested that rAAV2 has a much slower rate of uncoating than rAAV6 and rAAV8 in hepatocytes. 83 Whether uncoating rates between these serotypes are a reflection of different routes of intracellular processing remains to be elucidated. A recent review has also suggested that the rate of intracellular processing and uncoating of viral vectors may critically affect host immunological response toward input capsids in the absence of new viral protein synthesis.…”
Section: Future Directionsmentioning
confidence: 99%